Risk Analysis of Implementation of Water Resource Construction Projects Based on Price Ratio of Offer to Owner Estimate - Bayu Purnama; Andreas Franskie Van Roy; Andreas Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Contractor selection is a decision characterized by multiple objectives. Project owners want to minimize possible project costs but they also want contractors to be able to complete work on time and meet acceptable quality standards. The methods used in this research are Questionnaire, Microsoft Excel, and Statistical Package for the Social Science (SPSS). The purpose of this research is to identify the risks that may or may occur in the implementation of water resources construction projects based on the bid price against the owner estimate to determine the actions that must be taken to prevent and handle the risks that occur in the implementation. The results of the analysis of the 27 (twenty-seven) risk variables above, several risk variables have a high value (high risk), meaning that the risk has the potential to occur in the implementation of water resources construction projects, both at the bid price < 80% owner estimate and the bid price > 80% owner estimate.